Readers building fictional worlds: visual representations, poetry and cognition - Giovanelli, Marcello (Wiley, 2017)
This article explores the complex nature of the literature classroom by drawing on the cognitive linguistic framework Text World Theory to examine the teacher's role as facilitator and mediator of reading. Specifically, the article looks at how one teacher used visual representations as a way of allowing students to engage in a more personal and less teacher-driven transaction with a poem and to encourage them to reflect on their own roles as active makers of meaning and knowledge in the classroom. The article shows how teachers can be mindful of the various contextual factors that can privilege and legitimise certain kinds of response in the classroom and be wary of external factors and pressures that can promote the idea of preconceived knowledge. The teacher in the case study presented was able to both facilitate the experience of reading poetry in an unmediated way and also develop her students' metacognition in relation to the reading process itself. The article shows how Text World Theory's status as a socio-cognitive grammar may be of benefit to teachers in understanding the nature of communicative interaction and literary transaction.